2022
DOI: 10.3390/ijms231911850
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in MAFLD Modeling with Human Cell and Organoid Models

Abstract: Metabolic (dysfunction) associated fatty liver disease (MAFLD) is one of the most prevalent liver diseases and has no approved therapeutics. The high failure rates witnessed in late-phase MAFLD drug trials reflect the complexity of the disease, and how the disease develops and progresses remains to be fully understood. In vitro, human disease models play a pivotal role in mechanistic studies to unravel novel disease drivers and in drug testing studies to evaluate human-specific responses. This review focuses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 200 publications
0
6
0
Order By: Relevance
“…Self-assembling stem cell-derived or organoid-derived tissues and bioprinted tissues simulate some of the complexity of a liver tissue microenvironment; however, these platforms are still in their infancy 40 42 . Advances in designing organoid-engineered human multicellular three-dimensional NASH models have shown promise, recapitulating features of steatosis, inflammation and fibrosis, including a biophysical readout of organoid stiffening that reflects the fibrosis severity 43 . Moreover, co-culturing pluripotent stem cell (PSC)-derived lineages might provide greater reproducibility in constructing liver-like microstructures.…”
Section: What Are the Limitations Of Our Current Approach To Drug Dev...mentioning
confidence: 99%
“…Self-assembling stem cell-derived or organoid-derived tissues and bioprinted tissues simulate some of the complexity of a liver tissue microenvironment; however, these platforms are still in their infancy 40 42 . Advances in designing organoid-engineered human multicellular three-dimensional NASH models have shown promise, recapitulating features of steatosis, inflammation and fibrosis, including a biophysical readout of organoid stiffening that reflects the fibrosis severity 43 . Moreover, co-culturing pluripotent stem cell (PSC)-derived lineages might provide greater reproducibility in constructing liver-like microstructures.…”
Section: What Are the Limitations Of Our Current Approach To Drug Dev...mentioning
confidence: 99%
“…Scientific evidence suggests that genetic factors strongly influence the development of MAFLD, and these factors overlap with those identified as factors for NAFLD and NASH (non-alcoholic steatohepatitis) ( 1 , 5 , 8 ). The patatin-like phospholipase domain-containing protein 3 gene ( PNPLA3 ), Membrane bound O-acyltransferase domain containing 7 gene ( MBOAT7 ), transmembrane 6 superfamily member 2 gene ( TM6SF2 ), and glucokinase regulator gene ( GCKR ) have been the most recognized genes involved in the pathogenesis of fatty liver diseases ( 9 , 10 ). PNPLA3 was the first NAFLD-related genetic variant (rs738409; I148M) identified that displays a robust association with the development and severity of NAFLD.…”
Section: Pathophysiological Processes In the Development Of Mafldmentioning
confidence: 99%
“…The limited availability of human-derived liver samples, as well as ethical constraints, have led many researchers to study the pathogenesis of NAFLD using immortalized cell lines, including HepG2, Hep3B, HuH7, HL7702, PAV-1, and LX-2. For primary cells and immortalized cells, a mixture of saturated and unsaturated free fatty acids (FFA) were commonly used to induce NAFLD; a typical ratio of FFA is mixture 1:2 (palmitic acid/oleic acid) because this mimics the dietary composition of fatty acids . Despite the fact that most of the above models have been used to detect potential therapeutic compounds in vitro , it is still not possible to fully mimic the pathological process associated with NAFLD.…”
Section: Nafld Models In Vivo and In Vitromentioning
confidence: 99%
“…For primary cells and immortalized cells, a mixture of saturated and unsaturated free fatty acids (FFA) were commonly used to induce NAFLD; a typical ratio of FFA is mixture 1:2 (palmitic acid/oleic acid) because this mimics the dietary composition of fatty acids. 32 Despite the fact that most of the above models have been used to detect potential therapeutic compounds in vitro, it is still not possible to fully mimic the pathological process associated with NAFLD. Consequently, cell cocultures and 3D multicellular organ culture models have been constructed to maximize replication of the hepatic microenvironment in vivo.…”
Section: Nafld Models In Vivo and In Vitromentioning
confidence: 99%